PENGARUH KOMPETENSI SUMBER DAYA MANUSIA DAN SISTEM PENGENDALIAN INTERN TERHADAP KUALITAS INFORMASI LAPORAN KEUANGAN DENGAN MODERASI PEMANFAATAN TEKNOLOGI INFORMASI - Sa’adah, Khotimatus; Sitawati, Riana; Subchan, Subchan (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2017)
This research is based on the phenomenon that happened recently wherethere are many cases of misappropriation of savings and loan cooperativefunds that reach millions of rupiah, plus the case of investment bodong.Mandiri Jateng Savings and Loan Cooperative, which is considered healthyas a report that when it was considered normal, turned out to be a buggyinvestment that disturbed its members reaching billions of rupiah (Mcwnews,2017)The population of this research is employees of savings and loancooperatives in Jepara district. The sample of this research is manager,accounting and teller. The sampling technique used is purposive samplingmethod with the number of samples that can be analyzed that is 78. Analyzerused to analyze the problems such as Moderated Regression Analysis (MRA),coefficient of determination and hypothesis testing by using SPSS.Based on the results of data processing found that the competence ofhuman resources on the quality of financial statement information has asignificant positive effect with the significance value of 0.011 <0.05 andinternal control system has a significant positive effect on the quality offinancial statement information with a significance value of 0.003 <0.05.While the variable utilization of information technology as a moderationvariable can not memoderating between variable competence of humanresources to the quality of financial statement information with significantvalue 0,477> 0,05 and utilization of information technology as moderationvariable also can not memoderating internal control system to qualityinformation of financial statement with significance value 0.644> 0.05.